Studi Eksperimental Pengaruh Substitusi Sebagian Agregat Kasar Dengan Recycled Coarse Aggregate (RCA) Terhadap Kuat Tekan Dan Kuat Tarik Belah Beton Mutu Normal - Putri, Yoleta Tri; Irianti, Laksmi; Sebayang, Surya; Noorhidana, Vera Agustriana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2022)
The availability of crude aggregates on the market is increasing, and the greater waste of the construction industry is concrete, one of which is testing Laboratory Materials and Construction, Engineering Faculty, Lampung University. Research is required to identify the compressive strength value, split tensile strength value, volume weight and the effect of the age correction factor of concrete when partial replacement of coarse aggregate with Recycle Coarse Aggregate (RCA) has a design compressive strength of 25 Mpa and the test object is a cylinder with a 150x300mm.Based on the analysis of research data, it was found that from each factor of concrete age 7, 14 and 28 days as well as variations in partial substitution of coarse aggregate with a content of 25%, 50% and 100% RCA experienced a decrease in the value of the compressive strength and split tensile strength of concrete at each test age compared to the content of the concrete 0% RCA. For compressive strength values with average values at the age of RCA content respectively 0%, 25%, 50% and 100%, namely the age of 7 days 23,03 MPa, 22,57 MPa, 18,63 MPa and 16,71 MPa, 14 days 28,29 MPa, 28,11 MPa, 27,48 MPa and 21,79 MPa and 28 days 28,53 MPa, 28,16 MPa, 27,90 MPa and 27,74 MPa. For the value of the split tensile strength of concrete with an average value at the age of RCA content of 0%, 25%, 50% and 100%, namely the age of 7 days is 2,40 MPa, 2,27 MPa, 2,09 MPa and 1,79 MPa, at 14 days 2,71 MPa, 2,67 MPa, 2,49 MPa and 1,92 MPa and at 28 days 2,81 MPa, 2,78 MPa, 2,72 MPa and 2,48 Mpa.